2023
DOI: 10.1001/jamasurg.2022.7502
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Reoperation for Recurrence After Elective Primary Groin and Ventral Hernia Repair by Supervised Residents

Abstract: ImportanceSurgical training involves letting residents operate under supervision. Since hernia repair is a common procedure worldwide, it is a frequent part of the surgical curriculum.ObjectiveTo assess the risk of reoperation for recurrence after elective primary groin and ventral hernia repair performed by supervised residents compared with that by specialists.Design, Setting, and ParticipantsThis nationwide register-based cohort study included data from January 2016 to September 2021. Patients were followed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…A recent study from the Danish Hernia Register found no significant difference in reoperation risk for recurrent groin hernia between supervised residents and specialists 23 . In a report from the Swedish Hernia Register, it was found that male patients are at greater risk of reoperation on for recurrent groin hernia when a surgical trainee exceeded a certain operation time, emphasizing the importance of structured supervision 24 .…”
Section: Discussionmentioning
confidence: 91%
“…A recent study from the Danish Hernia Register found no significant difference in reoperation risk for recurrent groin hernia between supervised residents and specialists 23 . In a report from the Swedish Hernia Register, it was found that male patients are at greater risk of reoperation on for recurrent groin hernia when a surgical trainee exceeded a certain operation time, emphasizing the importance of structured supervision 24 .…”
Section: Discussionmentioning
confidence: 91%
“…Some caution in applying these findings to GME policy is advised in light of the growing concerns that graduates may be leaving residency programs unprepared to enter independent practice. 6 23 , 25 One approach is to change how residents are supervised to promote greater contacts with surgical attendings while maintaining the resident’s increasing autonomy during the procedure. 7 On the other hand, a separate study using electronic health records of VA medical centers between 2004 and 2019 showed clinical productivity of surgery residents net of supervision had increased over time consistent with a progressive independence hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“… 1 3 To address this question, academic leaders often cite studies reporting patients receive better medical 11 , 12 and surgical care 13 , 14 in teaching than nonteaching clinical settings. Surgery encounters involving a scrubbed resident have been found to have no worse outcome than those that either did not involve a resident or the resident was not scrubbed with respect to mortality, 8 , 9 , 15 18 complications, 8 , 9 , 15 , 19 22 readmissions and reoperations, 15 , 17 19 , 23 patient satisfaction, 21 or pain scores. 22 …”
mentioning
confidence: 99%
“…In "Risk of Reoperation for Recurrence After Elective Primary Groin and Ventral Hernia Repair by Supervised Residents," Christophersen et al demonstrate that involvement of surgical residents in primary hernia repairs had no significant impact on reoperation rates. 1 Because of the addition of supervision as a recorded variable in the Danish database, the authors were able to pair surgical outcomes with the dichotomous (presence or absence) value of supervision. Complexity was recorded based on several patient or operative characteristics.…”
Section: Kyla Terhune MD Mbamentioning
confidence: 99%